ANALYSIS OF LEGAL PROVISIONS DEFINING CRIMINAL LIABILITY FOR ENVIRONMENTAL CRIMES IN CIS MEMBER STATES - S. Sh. Utemuratova (Web of Journals Publishing, 2024)
This article analyzes the legal provisions defining criminal liability for environmental crimes in the criminal legislation of the Commonwealth of Independent States (CIS) member states. The study highlights the general principles and differences within the criminal legislation of CIS countries and examines the distinctive features of legislation in establishing liability for environmental offenses.
Keywords: Environmental crimes, CIS member states, criminal legislation, liability, environmental offenses, legislative analysis, environmental security, legal harmonization.